Tobacco cessation in Vietnam: Exploring the role of village health workers. Issue 9 (2nd September 2018) - Nguyen, Nam; Nguyen, Trang; Chapman, Jessica; Nguyen, Linh; Kumar, Pritika; VanDevanter, Nancy; Shelley, Donna
ABSTRACT: The purpose of this study was to explore current tobacco use treatment (TUT) practice patterns, and attitudes and beliefs among Village Health Workers (VHWs) about expanding their role to include delivering smoking cessation interventions and the perceived barriers. We conducted a survey of 449 VHWs from 26 communes in Thai Nguyen province, Vietnam. We assessed TUT practice patterns including asking about tobacco use, advising smokers to quit, offering assistance (3As) and attitudes, self-efficacy, and norms related to TUT. Seventy two per cent of VHWs reported asking patients if they use tobacco, 78.6% offered advice to quit, and 41.4% offered cessation assistance to few or more patients in the past month. Self-efficacy was low, with 53.2% agreeing that they did not have the skills to counsel patients about smoking cessation. The most commonly reported barriers to offering TUT were a lack of training and perceived lack of patient interest. Greater awareness of their commune health centre's smoke-free policy and higher levels of self-efficacy were associated with screening and offering cessation assistance. VHWs support an expanded role in tobacco cessation, but require additional resources and training to increase their self-efficacy and skills to provide effective treatment.